2010
DOI: 10.1002/syn.20866
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic modulation of the caudal photoreceptor in crayfish

Abstract: In our study we investigated the influence of dopamine (DA) on the caudal photoreceptor (CPR) in crayfish. Here we report the following: (a) the chromatographic determination of DA in the sixth abdominal ganglion (6th AG) shows a variation in the content during a 24-h cycle with the maximum value at dawn. (b) There are possibly dopaminergic neurons in the 6th AG with antityrosine hydroxylase antibodies. Immunopositive neurons (164) were located in the anterior and posterior regions of the 6th AG with the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…). Before light adaptation with 10 μ m SCH23390 DA 1 receptor antagonist (Rodriguez‐Sosa et al ., ), 77.8% of the trials of DD animals showed positive phototaxis (35 of 45 trials for seven animals). After light adaptation with SCH23390, these animals still showed positive phototaxis (70%: 49 of 70 trials) (SCH23390 in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…). Before light adaptation with 10 μ m SCH23390 DA 1 receptor antagonist (Rodriguez‐Sosa et al ., ), 77.8% of the trials of DD animals showed positive phototaxis (35 of 45 trials for seven animals). After light adaptation with SCH23390, these animals still showed positive phototaxis (70%: 49 of 70 trials) (SCH23390 in Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Rodriguez‐Sosa et al . (, ) also examine the role of both serotonin and dopamine in caudal photoreceptor of the crayfish terminal abdominal ganglion. Nevertheless, the interacting effects of serotonin and dopamine on phototaxis were unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Circadian rhythms have been reported in a variety of physiological functions of crayfish ranging from behavioral [37-39,41,43] to cellular [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and molecular levels [12][13][14][15][16][17][18][19]. Many of these are thought to be under the control of endogenous circadian oscillators.…”
Section: Discussionmentioning
confidence: 99%
“…Crustaceans have been known to show circadian rhythms in hormonal secretion [12][13][14][15], neurosecretion [16], biogenic amine contents and actions in the central nervous system [17][18][19], mechanoreceptor sensitivity [20], photoreceptor sensitivity [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and locomotor activity [37][38][39][40][41][42][43]. A previous study in the crayfish Procambarus clarkii showed that the circadian rhythm in leg movement disappeared when the circumesophageal commissures were surgically lesioned bilaterally, thus experimentally demonstrating the importance of descending signals from the brain to posterior ganglia [38].…”
Section: Introductionmentioning
confidence: 99%